Biomechanical analysis of some variables and EMG of the muscles during the performance of the snatch lift in weightlifting - Abdulwahab Ismaeel, Safaa; Hashim Fenjan, Falih; Habib Qadori, Rafid (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the relationship between some indicators of the electrical activity of the muscles (EMG peak) recording over skin (sEMG). This research is an important experiment in the field of producing high physical strength with perfect body performance for weightlifters as a final result of physical work characterized by strength and accurate performance. The research subject was eight of the best regional and national weightlifters (21 years ± 0.63), (79 kg ± 2.3), to record their experimental data in a descriptive way. The researchers using the four-channel wireless device produced by the Canadian company (Noraxon) for EMG, The research targeted the muscles (quadriceps femoris left and right) and (large dorsal muscle left and right). Also used high-speed video recording (210 f/s) Exillime Japanese camera for movement analysis. A force platform was used, Germany Zebris product, for recording the force transfer from foot to ground during the lift phases. The results showed significant symmetry relations between force and dorsal muscle. Also, the amount of force product is directly proportional with quadriceps EMG (left and right) and correspondingly with back dorsal muscle. The results showed that the increase in the speed of the lift (the end of the acceleration phase) is offset by a decrease in the amount of force on the ground and EMG of quadriceps. At the last phase (braking and fixation phase), the force and EMG came at the highest level.